2018
DOI: 10.1007/s13187-018-1394-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Health Belief Model-Based Intervention on Breast Cancer Screening Behaviors among Health Volunteers

Abstract: Breast cancer is the most common cancer and the second leading cause of death among women. Regarding the lack of knowledge about the cause of breast cancer and considering the fact that all women are prone to this disease, training on methods of early diagnosis to reduce its complications is of great importance. Thus, this study aimed to determine the effect of education based on the health belief model on breast cancer screening behaviors in health volunteers of health centers in Isfahan. In this experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 25 publications
18
24
1
Order By: Relevance
“…In contrast, some studies have reported that educational interventions were effective in improvement of the participants' belief in the severity of the consequences of breast cancer or their perceived severity. For instance, some studies carried out in Iran disclosed that the education based on HBM were effective in perceived severity [ 31 , 38 ]. Perceived severity can act as a double-edged sword; in case of excessive perceived severity, ignorance or non-performance of preventive behaviors may occur [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, some studies have reported that educational interventions were effective in improvement of the participants' belief in the severity of the consequences of breast cancer or their perceived severity. For instance, some studies carried out in Iran disclosed that the education based on HBM were effective in perceived severity [ 31 , 38 ]. Perceived severity can act as a double-edged sword; in case of excessive perceived severity, ignorance or non-performance of preventive behaviors may occur [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, some studies carried out in Iran disclosed that the education based on HBM were effective in perceived severity [ 31 , 38 ]. Perceived severity can act as a double-edged sword; in case of excessive perceived severity, ignorance or non-performance of preventive behaviors may occur [ 38 ]. This might be the reason for the increase in the performance of self-examination in the present study in spite of the fact that the intervention had no considerable effects on the perceived severity.…”
Section: Discussionmentioning
confidence: 99%
“…The model has been widely used in the production of effective and successful public health messaging. For example, the HBM was used to develop educational interventions to encourage breast cancer screening [ 11 ] and materials to promote weight-management [ 12 ]. It has also been employed as a tool for investigating health behaviour determinants, such as those that affect regular dental attendance among primary school-aged children [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…One is the health belief model (HBM) that is used as the theoretical framework in numerous educational interventions. HBM has proven to be effective in improving factors impacting BCS behaviors [7,[11][12][13][14]. The theoretical framework of the HBM emphasizes that threats pertaining to health concerns can negatively affect the health behavior of women.…”
Section: Introductionmentioning
confidence: 99%